Research utilization in municipality nursing practice in rural districts in Norway: a cross-sectional quantitative questionnaire study - Aud Moe; Ingela Enmarker (BMC, 2020)
Abstract Background Scientific knowledge and theory constitute part of the nurse's competence and evidence-based nursing practice. To obtain and maintain these skills, nurses require access to research utilization. The aim of the present study was therefore to describe and compare nurses in nursing homes and home-based nursing care and their use of research knowledge in their practice in elderly care in Norwegian rural districts. Methods The Research Utilization Questionnaire (RUQ) was employed in cross-sectional quantitative design. One hundred nurses were recruited from ten rural municipalities that participated in the study. Inclusion criteria for participating were registered nurses and employees working in the municipal elderly care service for 6 months or more. Results Most participants were younger than 55 years old, worked in permanent jobs, and were educated more than 5 years ago. The result showed that nurses in nursing homes were significantly more positive compared to nurses in home-based nursing care when analyzing all three domains in the RUQ together, as well as for attitudes towards research when testing each domain separated. Overall, each item in the domains revealed opinions that were more positive for nurses in nursing homes. The regression analysis showed that attitudes towards research, as well as availability and support of research utilization predicted the use of research in daily practice. Conclusions Positive attitudes, availability, and support for research utilization can contribute to greater use of research in nursing practice and improve the quality of service. Younger nurses' knowledge about using research should be shared with senior colleagues, who possess much experience in practice. In collaboration, they can develop evidence-based practice by the implementation of research seen in the context of nurses' experiences, user involvement, and person-centred practice. The i-PARIHS (Promoting Action on Research Implementation in Health Services) framework can be a useful tool in this implementation process.